Effect of chelated manganese on growth performance and carcass characteristics of finishing pigs - L J Kats; K G Friesen; K Q Owen; B T Richert; Jim L Nelssen; Robert D Goodband; Michael D Tokach; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1994)
A total of 80 medium-lean growth crossbred barrows (initially 77 lb) was used in a study to evaluate the effect of manganese level (24, 44, or 88 ppm) and source (inorganic vs chelated manganese) on growth performance and carcass characteristics of finishing pigs. Barrows were allotted by weight to pens containing two pigs per pen in a randomized complete block design. Pigs were assigned to one of four dietary treatments with 10 replications per treatment. Pigs were housed in pens (5 ft x 5 ft) in an environmentally regulated finishing barn and allowed ad libitum access to feed and water. Pigs were fed a corn-soybean meal-based diet formulated to contain .8% lysine and providing 24 ppm of inorganic Mn supplied from manganese oxide (control). Additional treatments included the control diet plus 20 ppm of a chelated form of Mn (a total of 44 ppm dietary Mn); control diet plus 20 ppm of inorganic Mn (manganese oxide; a total of 44 ppm dietary Mn); and the control diet plus 64 ppm of inorganic Mn (manganese oxide; a total of 88 ppm dietary Mn). Pigs were fed their respective experimental diet for the entire study. Pigs and feeders were weighed every 2 weeks to measure Average daily gain (ADG), average daily feed intake (ADFI), and feed conversion (F/G) until the mean weight of pigs in a pen averaged 225 lb. At this time, both pigs in the pens were slaughtered, and standard carcass measurements were recorded. For the overall trial, no differences occurred in growth performance among pigs fed any of the experimental treatments. Pigs had mean ADG, ADFI, and F/G of 2.10 lb, 6. 881b, and 3.24, respectively. No differences occurred in carcass traits, with all pigs having approximately 1.20 inches of backfat and between 4.50 and 5.0 square inches of longissimus muscle area. In conclusion, additional manganese above 24 ppm from an inorganic or chelated source had no effect on growth performance or carcass characteristics of medium-lean growth finishing pigs.; Swine Day, Manhattan, KS, November 17, 1994
Keywords: Swine day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-175-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 717; Swine; G/F; Manganese; Performance; Pig